65.8k views
17 votes
X - y = 11 and 3x + 10y = -6 How would I solve by substitution?

User Allexj
by
4.9k points

2 Answers

6 votes

Answer:

use the first equation and solve for the variables

Explanation:

for example, to solve for x add y on both sides x=11+y and substitute that to the equation

3(11+y)+10y=-6

that should give you -3

then go back to the equation x=11+y

x=11+(-3)

x=8

hope this helps!

User Diffeomorphism
by
4.8k points
6 votes

Answer:

y = - 3, x = 8

Explanation:

x - y = 11, x = 11 + y

Lets solve this equation with substitution: 3x + 10y = - 6

3(11+y)+10y=-6

33+3y+10y=-6

13y=-39

y = - 3

x - (-3) = 11

x + 3 = 11

x = 8

User Benny
by
5.4k points